Marine Biodiversity as an Attraction to Tourist in Seribu Islands in DKI Jakarta Province Indonesia - Mariati, Sri; Andri, Andri; Habibie, Fachrul Husain; Muhardiansyah, Doni; Mumin, Adhi Trirachmadi (Universitas Bina Sarana Informatika, 2023)
Pramuka Island is one of the islands in the Thousand Islands cluster. This island is included in the Panggang Island Village and is the administrative and government center of the Thousand Islands Administrative District. The purpose of this study is to identify the potential for diving tourism in the surrounding Pramuka Island. The research method used is a qualitative approach with a survey research design, direct observation methods, and interviews with dive guides who have had a career as dive guides on Pramuka Island for more than 20 years. The results of this study found that there were 30 natural tourist spots with marine biodiversity being the main attraction for diving tourism. We assessed the potential in 5 favorite spots, namely finding at a depth of 2-18 meters dominated by Acropora sp coral, Massive sp coral, Foliose, Fan coral (Gorgonian sea fan), and there are coral transplants at a depth of 2 meters). The types of fish found were Baraccudasp, yellow tail fish (casionida), Anemon fish (nemo), Damselfish, and Schooling anchovies), and Hawksbill Turtles. For 25 meters deep found Fish Shelter, Grouper Fish, Snapper Fish, and transparent shrimp. Marine diversity on Pramuka Island is a great potential for marine tourism, but sustainable and scientifically based management must be implemented to maintain the sustainability of marine resources and tourist attractions.